Rape at the Opera Staging Sexual Violence - Cormier, Margaret (Music and Social Justice, 2024)
The most-performed operas today were written at least a hundred years ago and carry some outdated and deeply problematic ideas. When performed uncritically, the misogyny, racism, and other ideologies present in many of these works clash with modern sensibilities. In Rape at the Opera, Margaret Cormier argues that production and performance are vital elements of opera, and that contemporary opera practitioners not only interpret but create operatic works when they put them onstage. Where some directors explicitly respond to contemporary dialogues about sexual violence, others utilize sexual violence as a surefire way to titillate, to shock, and to generate press for a new production. Drawing on archival footage as well as attendance at live events, Cormier analyzes productions of canonic operas from German, Italian, and French traditions from the eighteenth to the early twentieth century, including Die Entführung aus dem Serail, Don Giovanni, La forza del destino, Un ballo in maschera, Salome, and Turandot. In doing so, Cormier highlights the dynamism of twenty-first-century opera performance practice with regard to sexual violence, establishes methods to evaluate representations of sexual violence on the opera stage, and reframes the primary responsibility of opera critics and creators as being not to opera composers and librettists but to the public.